Examining The Effect of Theory of Planned Behavior on Individual Investment Intention in The Indonesia Stock Exchange, Moderated by Herding Behavior and Risk Propensity - Eka Bertuah; Hotman Dufeb Halomoan Oppusunggu (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
There are several products or instruments traded on the Indonesia Stock Exchange, that is Stocks, Bonds, Mutual Funds, Exchange Traded Funds (ETFs), and Derivatives, with stocks being the most popular instrument right now. The benefits of the existence of the capital market for investors are that it provides an opportunity for the public to have a healthy company that has good prospects in the future, and is an alternative investment beside gold and properties that provides potential profits with calculated risks (Kurniawan, 2019).Objectives: This study aims to determine the effect of the construct variable of the Theory of Planned Behavior on Investment Intention, and the role of Investment Intention as a mediating variable that connects these variables after being moderated by Risk Propensity and Herding Behavior on Investment Behavior of individual investors in IndonesiaMethodology: This study uses primary data which data was collected by distributing online questionnaires via google form.  This research was conducted from January to March 2022, from a sample of individual investors from some big islands in Indonesia (Java, North Sumatra, South Sulawesi, Kalimantan). To determine the sample, this study uses the Slovin formula with probability sampling technique - simple random and a total of 525 respondents were collected, but those who met the predetermined sample criteria were 468 respondents. The data analysis that is used is the path analysis Structural Equation Model (SEM).Finding: Herding behavior and Risk Propensity do not strengthen Investment Intention among individual investors towards Investment Behavior and can be a subject for further study.Conclusion: The results of this study is only that Product Involvement of Theory of Planned Behavior variables can positively influence Investment Intention. Furthermore, Investment Intention can mediate this variable on Investment Behavior, although not strengthened by the influence of Risk Propensity and Herding Behavior